Max Frisch: Tagebuch 1946-1949 y Tagebuch 1966-1971. «Literarisches Tagebuch als Kunstform» - Martí Peña, Ofelia (Revista de Filología Alemana, 2002)
Max Frisch’s Diary 1946-1949 and the Diary 1966-1971 established a model of literary Diary where the autobiographical function, characteristic of this form, and the artistic function are both involved. In this paper there is a first part dedicated to define the several characteristics of a literary Diary. In the second part technical resources according to which Max Frisch arranges in sequences the different parts ficticious as well as autobiographical— of the first Diary 1946-1949 are analised and treated. Topical cores and spatial setting reach there a special relevance. In the third part, the second Diary 1966-1971 is analised in the same way as the first one: The text arrangement and the use of different types of letter are here specially relevant as composition elements. After analising both Diaries we are able to confirm the hypothesis we had stated at the beginning: that the Diary 1946-1949 and the Diary 1966-1971 are actually literary texts produced and created as artistic/literary works. And there is no trace of an autobiographical aim in the work neither in its specific parts.